(untitled) - Trefil, James S. (New York, 1998)
Within this text, the authors explore the main aspects of physical and life sciences and will show how to integrate these scientific principles into everyday life and events. The reader/student will examine such issues as human health, technology, environmental concerns and more.
Keywords: Science,Khoa học; Study and teaching (Higher),Nghiên cứu và giảng dạy (cao hơn)